Machine learning for business analytics : concepts, techniques and applications in R.: concepts, techniques and applications in R. (2023) - Shmueli, Galit, 1971-; Bruce, Peter C, 1953-; Gedeck, Peter; Yahav, Inbal; Patel, Nitin R (Nitin Ratilal)
No abstract available